Perception of possible sars-cov-2 infection and associated complications in seven labor sectors in peru - Mejia, Christian R. (2020)
Objective: To determine the perception of possible infection caused by the severe acute respiratory syndrome coronavirus (SARS-CoV-2) and associated complications according to the labor sector in Peru. Methods: We performed an observational, cross sectional, and secondary data analysis. The study had three dependent variables that were obtained from a locally validated questionnaire, in which it is asked whether the professionals had the perception that they could be infected with SARS-CoV-2 at work, or could transmit the virus to their family/friends, and regarding the possibility of complications related to the infection. Results: Of the 2843 workers participating in the study, those in the health sector perceived that they were more likely to be infected at work. In the multivariate analysis, adjusted for four variables, health sector workers also perceived that they could be infected more frequently at work (adjusted prevalence ratio (aPR): 1.74; 95% confidence interval (CI): 1.40-2.15; p <0.001). These professionals, moreover, perceived that they could transmit the virus to their family/friends (aPR: 0.76; 95% CI: 0.63-0.92; p = 0.005) or that there would be complications resulting from the infection (aPR: 0.59; 95% CI: 0.48-0.73; p <0.001). On the other hand, engineering sector workers were the ones who had a greater perception that they could infect their family/friends (aPR: 1.95; 95% CI: 1.20-3.20; p = 0.007), while workers from other sectors perceived that they could have more chances of complications from the infection (aPR: 1.17; 95% CI: 1.05-1.30; p = 0.006). Conclusion: The health sector may be the most vulnerable in this context, which is why occupational health teams should develop and implement specific surveillance plans to prevent and reduce the number of coronavirus disease 2019 (COVID-19) cases among healthcare workers.